Insulin stimulates choline acetyltransferase activity in cultured embryonic chicken retina neurons. - Kyriakis, J M (1987)
The effect of insulin on the appearance of the enzyme choline acetyltransferase (ChoAcT; acetyl-CoA:choline O-acetyltransferase, EC 2.3.1.6) in embryonic chicken retina neurons cultured in defined medium was studied. In the presence of a minimal level of insulin (1 ng/ml), ChoAcT activity increased with time in culture. A correspondence between the insulin concentration in the defined medium (1-100 ng/ml) and both the rate of increase and maximum attained level of ChoAcT activity was observed. Maximal ChoAcT activity was 2- to 3-fold greater in cells cultured in the presence of 100 ng of insulin per ml than in cells cultured in the presence of 1 ng of insulin per ml. To elicit maximum ChoAcT activity, insulin at 100 ng/ml was required in the medium for only the first 4 days of the culture period, at which time insulin could be reduced to maintenance levels (10 ng/ml) without affecting ChoAcT activity. Insulin binding assays performed during a 7-day culture period revealed that irrespective of the insulin concentration in the medium during culture, cell-surface insulin receptors decreased by approximately 90% between 4 and 7 days in culture. This decrease in insulin binding corresponded to the observed decrease in the sensitivity of ChoAcT activity to insulin. Our findings suggest that insulin plays a role in mediating cholinergic differentiation in the embryonic chicken retina.